TEA HF laser with a high specific radiation energy; Proceedings of SPIE; Vol. 10254 : High Power Laser Systems and Applications - Puchikin A. V. Aleksey Vladimirovich; Andreev M. V. Mikhail Vladimirovich; Losev V. F. Valery Fedorovich; Panchenko Yu. N. Yury Nikolaevich (2017, 2017)
Title screen